A fanpage of sexual and reproductive health education with good information quality: Youth perception - Hidayat M.T.; Fauziati E.; Nugroho A.; Mokhtar R.H.B. (Inderscience Enterprises Ltd., 2024)
Indexed by Scopus/ERA